Safety around strangers - Raatma, Lucia (Mankato, MN : Bridgestone Books, 1999)
Provides a definition of strangers and ways to be safe around them as well as suggestions on where to go for help if needed.
Includes bibliographical references (p. 24) and index.
Keywords: Safety education -- Juvenile literature; Children and strangers -- Juvenile literature; Kidnapping -- Prevention -- Juvenile literature; Safety; Strangers; Kidnapping -- Prevention